An analytical model for predicting the shielding effectiveness and resonances of a lossy enclosure with apertures. Issue 4 (4th March 2022) - Gong, Yanfei; Chen, Xingtong
Abstract : In this paper, an improved analytical model is presented to predict the shielding effectiveness (SE) and resonances of an apertured enclosure composed of the material of finite conductivity. In the model, the modified parameters of the rectangular waveguide are introduced to deal with the lossy enclosure with apertures, which can consider the effects of wall loss on the SE. Firstly, according to the circuit theory and electromagnetic topology (EMT) theory, the lossy enclosure is modeled as the circuit model and signal flow graph, respectively. Then, the electric field components at the monitor point can be obtained; hence, the SE can be predicted accurately. Finally, the presented model is utilized to analyze the effects of various parameters and conditions on the SE. The validity of the presented model is verified by the CST through several cases, showing that the lossy enclosure is feasible to damp all the resonant modes.